Exploring the role of economics in prioritization in public health: what do stakeholders think? - Jaynie Rance (The European Journal of Public Health, 2011)
Background: Debates surrounding the use of conventional approaches in public health and the existence of perceived barriers to using the results of economic evaluations have led to questions posed as to how to establish priorities within public health schemes. The aims of this study were therefore to explore the feasibility and validity of economic evaluation techniques in developing priorities within public health programmes and consider the extent to which different presentational approaches are likely to be incorporated into decision-making, from perspectives of relevant stakeholders. Methods: An advisory board, representative of potential users of economic evaluations, was set up to identify preferences for how findings from economic evaluations might be presented to decision makers and to test the impact of different approaches, different outputs and different presentational styles. The board was divided into two groups, each of which was given three hypothetical ‘scenarios’ to consider. The scenarios comprised descriptions of methods and outputs, with costs, effects, target population and context of intervention constant across all scenarios. Results: The perceived validity of estimates of effectiveness was vitally important, along with sufficient information to gauge whether designs were appropriate and to assess implementation practicalities. Cost–benefit analysis and cost–utility analysis were the preferred approaches despite their complexity, although participants required benchmarks to place net-benefit estimates from cost–benefit analyses into context. Conclusion: Further research is required to substantiate and build on these preliminary findings and collaborations between economists and policy makers are needed to develop clear, rigorous and standard guidance relating to economic evaluation, recognizing the diversity of public health strategies.